2015
DOI: 10.1007/s11356-015-4773-3
|View full text |Cite
|
Sign up to set email alerts
|

Chemical behavior of Cu, Zn, Cd, and Pb in a eutrophic reservoir: speciation and complexation capacity

Abstract: This research aimed at evaluating cadmium (Cd), copper (Cu), lead (Pb), and zinc (Zn) speciation in water samples as well as determining water quality parameters (alkalinity, chlorophyll a, chloride, conductivity, dissolved organic carbon, dissolved oxygen, inorganic carbon, nitrate, pH, total suspended solids, and water temperature) in a eutrophic reservoir. This was performed through calculation of free metal ions using the chemical equilibrium software MINEQL+ 4.61, determination of labile, dissolved, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…These results indicate that even in concentrations as low as those found in the environment (Tonietto and Grassi , Tonietto et al. , Asare et al. ), microalgae can face difficulties, with the cell division process being impaired.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…These results indicate that even in concentrations as low as those found in the environment (Tonietto and Grassi , Tonietto et al. , Asare et al. ), microalgae can face difficulties, with the cell division process being impaired.…”
Section: Discussionmentioning
confidence: 86%
“…Natural dissolved organic materials present in freshwaters complexes copper (Buffle ), and in such waters, free copper ions are detected in the order of 10 −9 to 10 −7 mol · L −1 (Mansilla‐Rivera and Nriagu , Wang and Chakrabarti , Tonietto et al. ).…”
mentioning
confidence: 99%
“…The concentration of dissolved oxygen in water could be used to determine water quality, since it directly affects aquatic biodiversity. Moreover, according to Valente, Padilha, andSilva (1997), Silv erio et al (2005), Zanata et al (2008), Rocha et al (2010), and Tonietto et al (2015), the water analysis revealed that Barra Bonita presents conditions that are unsuitable for aquatic life.…”
Section: Discussionmentioning
confidence: 99%
“…The time residence of BB varies between 30 (summer) to 180 days (winter), whereas in the BAR it ranges between 7-24 days. Both reservoirs are considered eutrophic systems, with recurrent microalgae blooms due to nutrient and pollutant discharges within the Tietê River driven by nearby urban areas [21][22][23][24][25].…”
Section: Tietê River Cascade System Of Reservoirs (Tcsr)mentioning
confidence: 99%